English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1 + cos2A = 2 / (1 + tan^2 A)

2006-12-02 11:23:37 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

1+cos2A=2/(1/cos^2A).....'cuz 1+tan^2A=1/cos^2A
1+cos^2A-sin^2A = 2cos^2A ......... 'cuz cos2A=cos^2A-sin^2A
cos^2A + cos^2A = 2cos^2A ......... 'cuz 1-sin^2A = cos^2A
2cos^2A = 2cos^2A

2006-12-02 11:41:11 · answer #1 · answered by albert 5 · 0 0

Ok, let's try this one...

tan(A) = sin(A)/Cos(A)

1 + tan^2(A) = 1+ sin^2(A)/cos^2(A)
= (cos^2(A) + sin^2(A))/cos^2(A)
= 1/cos^2(A)

2/(1/cos^2(A)) = 2cos^2(A)

now, working with the 1 + cos2A,

cos(A+A) = cos(A)cos(A) - sin(A)sin(A) = cos^2(A) - sin^2(A)
and
1 = cos^2(A) + sin^2(A)

1+ cos2A = 2 cos^2(A)

Good luck!

2006-12-02 19:34:23 · answer #2 · answered by alrivera_1 4 · 0 0

1 + cos(2A) = 2/(1 + tan(A)^2)
1 + cos(2A) = 2/(1 + (sinA/cosA)^2)
1 + cos(2A) = 2/((cos(A)^2 + sin(A)^2)/(cos(A)^2))
1 + cos(2A) = 2/(1/cos(A)^2)
1 + cos(2A) = 2cos(A)^2

cos(2A) = 2cos(A)^2 - 1

1 + cos(2A) = 2cos(A)^2
cos(2A) = 2cos(A)^2 - 1

2006-12-02 21:54:06 · answer #3 · answered by Sherman81 6 · 0 0

1+2cos^A-1
=2cos^2A
=2/sec^2A
=2/(1+tan^2A)

2006-12-02 19:34:19 · answer #4 · answered by raj 7 · 0 0

fedest.com, questions and answers